Lives and livelihoods trade-offs: Which COVID-19 strategies for which countries? - Vu Minh Ngo; Huan H. Nguyen; Hien Thu Phan; Phương Thanh Thi Tran (Cogent Economics & Finance, 2022)
Are COVID-19 non-pharmaceutical interventions (NPIs) at the expense of economic outcomes? Furthermore, given the heterogeneities in macroeconomic conditions, should countries follow a unified COVID-19 strategy such as "No-COVID"? This study provides cross-country evidence that attempts to address these critical questions during the pandemic era. Given the substantial heterogeneity in unemployment rates of OECD countries, it is necessary to understand the effects of NPIs' implementation, which could vary widely across conditional quantiles of unemployment rates. Using monthly data from OECD countries from February 2020 to June 2021 and quantile regression analysis for panel data (QRPD), we explore the impacts of NPIs on economic outcomes. The results indicate that NPIs effectively contained the pandemic and had substantial positive impacts on low quantiles of unemployment rates. However, at high quantiles of unemployment rates, the trade-off is viable and significant. In addition, countries' vaccination policies and scales also predict their economic outlooks, especially when combined with non-pharmaceutical interventions. Based on these findings, this study suggests different COVID-19 strategies for different groups of countries according to their macroeconomic settings. The trade-off between lives and livelihoods is much more troublesome and prevalent in countries with unfavorable macroeconomic conditions and hinders them from pursuing strategies such as "No-COVID".
Keywords: 330; non-pharmaceutical interventions; vaccination campaign; COVID-19; trade-offs; public health; unemployment rate